2013
DOI: 10.1128/aem.03793-12
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Inferences Reveal a Large Extent of Novel Biodiversity in Chemically Rich Tropical Marine Cyanobacteria

Abstract: bBenthic marine cyanobacteria are known for their prolific biosynthetic capacities to produce structurally diverse secondary metabolites with biomedical application and their ability to form cyanobacterial harmful algal blooms. In an effort to provide taxonomic clarity to better guide future natural product drug discovery investigations and harmful algal bloom monitoring, this study investigated the taxonomy of tropical and subtropical natural product-producing marine cyanobacteria on the basis of their evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 51 publications
3
89
0
2
Order By: Relevance
“…Although some cyanobacteria, such as Synechococcus sensu lato, lack phenotypic variability, great ecological and genetic diversity suggest that polyphyletic complexes of cryptic taxa might exist (Honda et al 1999;Robertson et al 2001;Dvořák et al 2014a, b). Many traditional cyanobacterial genera (Geitler 1932) are polyphyletic (Komárek 2010;Engene et al 2011;Hašler et al 2012;Engene et al 2013;Dvořák et al 2014a, b;Hašler et al 2014a) and need extensive revisions, which will be very difficult particularly in the case of Synehococcus sensu lato due to extreme polyphyly within this genus. We suggest that this extreme polyphyly (cryptogenera sensu Komárek et al 2014) should be distinguished from polyphyly in the original sense, since in extreme polyphyly a large number of lineages derived over very long time period (over 3 billion years), as shown in Dvořák et al (2014b).…”
Section: Particular Problems Of Species Definitions and Concepts In Cmentioning
confidence: 99%
“…Although some cyanobacteria, such as Synechococcus sensu lato, lack phenotypic variability, great ecological and genetic diversity suggest that polyphyletic complexes of cryptic taxa might exist (Honda et al 1999;Robertson et al 2001;Dvořák et al 2014a, b). Many traditional cyanobacterial genera (Geitler 1932) are polyphyletic (Komárek 2010;Engene et al 2011;Hašler et al 2012;Engene et al 2013;Dvořák et al 2014a, b;Hašler et al 2014a) and need extensive revisions, which will be very difficult particularly in the case of Synehococcus sensu lato due to extreme polyphyly within this genus. We suggest that this extreme polyphyly (cryptogenera sensu Komárek et al 2014) should be distinguished from polyphyly in the original sense, since in extreme polyphyly a large number of lineages derived over very long time period (over 3 billion years), as shown in Dvořák et al (2014b).…”
Section: Particular Problems Of Species Definitions and Concepts In Cmentioning
confidence: 99%
“…To date, however, there are no reports of marine cyanobacterial blooms in the Colombian Caribbean (particularly planktonic blooms), although several species have been recorded in floristic lists in the region (Díaz-Pulido & Díaz-Ruíz 2003, Reyes et al 2013. Benthic cyanobacterial mats in Old Providence, consisted of complex consortia belonging to the genera Okeania, Lyngbya, Symploca, Phormidium and Oscillatoria which have also been reported in other tropical areas (Hamisi et al 2004, Thacker & Paul 2004, Charpy et al 2010, Engene et al 2013a. At Old Providence Island, as well as in other Colombian Caribbean reefs off the continental shelf such as Rosario Islands and Barú, cyanobacteria have become more conspicuous, frequently surpassing live coral cover (Puyana M & Acosta A, unpub.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this paper we report the most common taxa found during field surveys after Komárek & Anagnostidis (2005) and Engene et al (2013b). During the period between 2011 and 2014 there has been a profound reevaluation of the group systematics beyond genera reassignment, showing great genetic diversity, and wide morphological and chemical variation (Thacker & Paul 2004, Engene et al 2010, Engene et al 2011, Engene et al 2013a, Engene et al 2013b). Blooms of marine benthic cyanobacteria are not monospecific and "accurate" species identification involves molecular and chemotaxonomical analyses.…”
Section: Samplingmentioning
confidence: 99%
“…The study identified deuterostome's lineage as the most promising metazoan lineage for the discovery of bioactive agents. Phylogenetics have also been successfully used to determine the target clades of cyanobacteria that produce natural products [21]. A study that constructed genus-level phylogenetic tree representing 20,000 species from three biodiversity hotspots revealed that traditional medicinal plant use is not scattered randomly but is concentrated in certain parts of the phylogenetic trees [22].…”
mentioning
confidence: 99%